A Pilot Study of Universal Teacher–Child Interaction Training at a Therapeutic Preschool for Young Maltreated Children. (November 2018) - Kanine, Rebecca M.; Jackson, Yo; Huffhines, Lindsay; Barnett, Alexandra; Stone, Katie J.
Young children are disproportionately exposed to maltreatment but are underrepresented in research on effective treatments. Universal Teacher-Child Interaction Training (TCIT-U), developed from Parent-Child Interaction Therapy, may be especially appropriate for maltreated children as they often experience caregiver disruptions which pose challenges to traditional parent-child treatment. Furthermore, research suggests that teachers can play an important role for children who lack positive caregiving experiences. The current study examined the effectiveness of TCIT-U versus treatment-as-usual (TAU) at a therapeutic preschool for youth exposed to maltreatment. Thirty-eight children (2–5 years old) and eight teachers from four classrooms participated in the study. Teacher behaviors were observed and coded at baseline, mid-treatment, post-treatment, and 3-month follow-up. Teachers reported on children's behavior and social-emotional skills at baseline, post-treatment, and 3-month follow-up. TCIT-U teachers demonstrated substantial increases in positive attending skills (PRIDE [Praise, Reflection, Imitation, Description, and Enjoyment] skills) and decreases in negative talk and questions during intervention phases, and these skills were maintained at follow-up. In addition, children in the TCIT-U classrooms demonstrated a significantly greater increase in overall social-emotional skills by post-treatment than children in the TAU classrooms, and effect sizes were moderate for all child outcomes. Findings provide preliminary support for TCIT-U's effectiveness in a therapeutic setting for children exposed to maltreatment.